1990
DOI: 10.1002/app.1990.070400108
|View full text |Cite
|
Sign up to set email alerts
|

Poly(styrene‐co‐acrolein) latex particles: Copolymerization and characteristics

Abstract: SynopsisReactive microspheres suitable for binding proteins were prepared using emulsifier-free emulsion copolymerizations of styrene (St) and acrolein (AL) with various molar ratios of monomers St and AL. A maximum polymerization rate was obtained when the molar ratio of the monomers was 1 : 1. The diameter of the latex particles increased with increase in the amount of monomer AL. The amounts of aldehyde groups on the latex particle surfaces were determined by conductometric titration. The binding capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 12 publications
1
28
1
Order By: Relevance
“…Since the aldehyde groups have the commercial device Zeta-Sizer 4 (Malvern Instruments, England). The electrophoretic mobility values were obtained no charge we followed the method of the hydroxylamine hydrochlorate reported by Yan et al (10). The titrations for by taking the average of (at least) six measurements at the stationary level in a cylindrical cell, changing the suspension AD-1 latex were shown and described in a previous paper (11).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Since the aldehyde groups have the commercial device Zeta-Sizer 4 (Malvern Instruments, England). The electrophoretic mobility values were obtained no charge we followed the method of the hydroxylamine hydrochlorate reported by Yan et al (10). The titrations for by taking the average of (at least) six measurements at the stationary level in a cylindrical cell, changing the suspension AD-1 latex were shown and described in a previous paper (11).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…and the amounts of the CHO surface groups were determined after acid cleavage of the acetals and The reaction mixture was kept for 1 h at room temperature to swell the seed particles with the titration with hydroxylamine hydrochloride. 4 The determination of the surface charge dentermonomers. Once the reaction temperature (70ЊC) was reached, the initiator aqueous solution sity (s) was made as follows: was charged into the reactor to start the polymerization.…”
Section: Methodsmentioning
confidence: 99%
“…Polymer latex particles ter of the test, the reactivity, and the stability of with adsorbed antibodies or antigens are used as immunoassays. carriers of diagnostic reagents for the clinical Recently some authors 4,7,8 have indicated that evaluation of a great variety of analytes. 1,2 A new the use of aldehyde groups on the surface of the generation of functionalized latex particles have latex particles could simplify the covalent bonding been synthesized to bond covalently the amino of the protein due to the direct reaction between groups of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three different slopes in the potentiometric curve (Fig. 3) caused by: (i) the titration of NaOH for neutralization of the HCl previously added, (ii) the titration of the carboxyl groups of the magnetic particles surface, and (iii) the excess of titration agent (NaOH).The amount of COOH groups on the surface is calculated from the break in curve and expressed in terms of milliequivalent of COOH groups per 1 g of the magnetic microspheres [20]:…”
Section: Ftir Analysis and Surface Functional Groupsmentioning
confidence: 99%